2021
DOI: 10.1038/s41598-021-90544-5
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass blue carbon stocks and sequestration rates in the Colombian Caribbean

Abstract: Seagrass ecosystems rank amongst the most efficient natural carbon sinks on earth, sequestering CO2 through photosynthesis and storing organic carbon (Corg) underneath their soils for millennia and thereby, mitigating climate change. However, estimates of Corg stocks and accumulation rates in seagrass meadows (blue carbon) are restricted to few regions, and further information on spatial variability is required to derive robust global estimates. Here we studied soil Corg stocks and accumulation rates in seagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
3
19
1
1
Order By: Relevance
“…At our site in 13 months within exclosures, the relative sediment level increased up to 4.4 cm, however long-term accretion rates at this site will be subject to compaction and they remain unknown at this time. C org content (%) in the surficial sediment at our tropical study site was similar to the reported 2% C org for seagrass sediment globally (Fourqurean et al, 2012), similar to the Pacific coast of Costa Rica (Samper-Villarreal et al, 2018a;Samper-Villarreal et al, 2020a;Samper-Villarreal and Corteś, 2020;Samper-Villarreal et al, 2022), and higher than meadows also dominated by T. testudinum in the Caribbean coast of Colombia (Serrano et al, 2021); thus indicating effective C org sequestration in seagrass sediment at our site. Similar to our findings, sediment C org content did not decrease at a simulated grazing experiment in the Bahamas which maintained canopy structural complexity low over 16 months in clipped plots (Moran and Bjorndal, 2005;Moran and Bjorndal, 2007).…”
Section: Seagrass Biomass and Sediment Carbon Poolssupporting
confidence: 86%
See 2 more Smart Citations
“…At our site in 13 months within exclosures, the relative sediment level increased up to 4.4 cm, however long-term accretion rates at this site will be subject to compaction and they remain unknown at this time. C org content (%) in the surficial sediment at our tropical study site was similar to the reported 2% C org for seagrass sediment globally (Fourqurean et al, 2012), similar to the Pacific coast of Costa Rica (Samper-Villarreal et al, 2018a;Samper-Villarreal et al, 2020a;Samper-Villarreal and Corteś, 2020;Samper-Villarreal et al, 2022), and higher than meadows also dominated by T. testudinum in the Caribbean coast of Colombia (Serrano et al, 2021); thus indicating effective C org sequestration in seagrass sediment at our site. Similar to our findings, sediment C org content did not decrease at a simulated grazing experiment in the Bahamas which maintained canopy structural complexity low over 16 months in clipped plots (Moran and Bjorndal, 2005;Moran and Bjorndal, 2007).…”
Section: Seagrass Biomass and Sediment Carbon Poolssupporting
confidence: 86%
“…More complex canopies decrease water flow and increase the deposition of suspended particles, thereby increasing vertical accretion of seagrass sediment (Kennedy et al, 2010). Short-and long-term sediment accumulation rates within seagrass meadows dominated by T. testudinum in the Colombian Caribbean range between 0.04 and 0.7 cm yr -1 (Serrano et al, 2021). Meanwhile, sediment accretion over the summer from experimental eelgrass transplantation in the Wadden Sea was 0.5-0.7 cm (Bos et al, 2007).…”
Section: Seagrass Biomass and Sediment Carbon Poolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nivel del Caribe colombiano esto cobra mayor importancia, teniendo en cuenta los datos registrados en Serrano et al (2021), los cuáles muestran una aproximación al cálculo del carbono en los sedimentos de los pastos marinos del país, destacando que el valor de los stocks en los sedimentos de La Guajira y San Andrés superan los promedios globales, alcanzando los 240 Mg C/ha. Esto, sumado a lo registrado por Guerra et al (2020) para San Andrés, donde se calculó que el valor de carbono en los sedimentos osciló entre 91 y 144 Mg C/ha, y lo hallado por Congdon et al (2017) y Gullström et al (2018), donde se evidenció que el contenido de carbono en sedimentos es más alto en zonas donde la cobertura y la biomasa tiende a ser mayor, refrenda el hecho de que la protección del sistema de biomasa aérea y subterránea repercute directamente en los reservorios de los sedimentos, y por ende en la optimización de los procesos de captura de carbono.…”
Section: Discussionunclassified
“…At level of the Colombian Caribbean, this becomes more important, taking into account the data recorded in Serrano et al (2021), which shows an approximation of the carbon values in the sediments of the country's seagrasses, highlighting that the stocks in the sediments of La Guajira and San Andrés exceed global averages, reaching 240 Mg C/ ha. This, added to the study from Guerra et al (2020) for San Andrés, where the value of carbon in the sediments ranged between 91 and 144 Mg C/ha, and the information reported by Congdon et al (2017) and Gullström et al (2018), where it was shown that the carbon content in sediments is higher in areas where coverage and biomass tend to be greater, endorses the fact that the protection of the aerial and underground biomass system has a direct impact on the reservoirs of sediments, and therefore in the optimization of carbon capture processes.…”
Section: Conclusionesmentioning
confidence: 97%